Microbial community analysis during start-up of anaerobic co-digestion based on quinone profiles using supercritical fluid extraction - Asri Gani; Ahmed Fall; Hiroyuki Daimon (Syiah Kuala University, 2011)
Quinone profile is well known as a useful tool for the analysis of microbial community dynamics in mixed cultures in terms of quantification, simplicity, and reproducibility. The application of quinone profile method in anaerobic digestion is to monitor and overcome instability during fermentation process. A lab-scale anaerobic digestion treating a mixture of milk cow manure (CM) and simulated food waste (FW) during start-up process at mesophilic conditions was used to monitor the change of microbial community dynamics and stability. Supercritical fluid extraction (SFE) experiments using CO2 and ultra-high performance liquid chromatography (UPLC) was applied for extract and determination of ubiquinones (UQ) and menaquinones (MK) species. Quinone can be a helpful tool to make the link between microbial community and anaerobic digestion parameters in order to overcome digester instability during the start-up process.